Family endowments and multidimensional poverty among urban older adults living alone - Yin, Xingxing; Cui, Jinghang; Bai, Ruirui; Wu, Yifan; Ma, Jiayue; Zhai, Yifei; Crandall, K. Jason (Frontiers in Public Health, 2025)
BackgroundDisparities in family endowments play a pivotal role in shaping the multidimensional poverty among urban older adults living alone (UOALA).MethodsThis study conducted an empirical analysis using data from 1,656 UOALA in five different cities in China to investigate the relationship between family endowments and the occurrence of multidimensional poverty among UOALA.ResultsThe findings illustrate an expanding and deepening scale of poverty among UOALA, particularly manifested in dimensions of physical health and mental well-being. Females, super-older adults, and those residing in non-first-tier cities exhibit higher levels of poverty incidence and depth. The study also reveals that while the number of children in a family does not significantly impact multidimensional poverty in UOALA, factors such as children’s proximity of residence and financial situation play a significant role. Moreover, gender differences are observed in the influence of sons and daughters on the poverty status of UOALA.ConclusionEnhancing family older adults care support capacity and improving societal welfare levels emerge as critical policy measures to prevent UOALA from falling into Multidimensional Poverty.